Microstructure and Electrical Property of Ex-Situ and In-Situ Copper Titanium Carbide Nanocomposites - Nguyen Hoang Viet (Metals, 2020)
In this study, ex-situ Cu-TiC nanocomposites of 1, 3 and 5 vol. % TiC and in-situ Cu-TiH2-C nanocomposites (corresponding to 5 vol. % TiC) were prepared using ball milling and spark plasma sintering methods. Powder mixtures were milled for 4 h at 400 rpm. As-milled Cu-TiC composite powders were consolidated under an applied pressure of 70 MPa. The phase composition, and microstructure of the composite samples were characterized by X-ray diffraction, and scanning electron microscope and transmission electron microscope techniques, respectively. With the increasing TiC content from 1 to 5 vol. %, the hardness of the ex-situ composites when sintered at 600 °C changed between 161.4 and 178.5 HV and the electrical conductivity decreased from 52.1 to 47.6 % IACS. In-situ Cu-TiH2-C nanocomposite sintered at 950 °C had higher hardness and electrical conductivity than ex-situ Cu-TiC composite due to having a homogenous distribution of nano reinforcement particles and dense structure.